Profile of Small RNAs, vDNA Forms and Viral Integrations in Late Chikungunya Virus Infection of Aedes albopictus Mosquitoes - Michele Marconcini; Elisa Pischedda; Vincent Houé; Umberto Palatini; Nabor Lozada-Chávez; Davide Sogliani; Anna-Bella Failloux; Mariangela Bonizzoni (Viruses, 2021)
The Asian tiger mosquito Aedes albopictus is contributing to the (re)-emergence of Chikungunya virus (CHIKV). To gain insights into the molecular underpinning of viral persistence, which renders a mosquito a life-long vector, we coupled small RNA and whole genome sequencing approaches on carcasses and ovaries of mosquitoes sampled 14 days post CHIKV infection and investigated the profile of small RNAs and the presence of vDNA fragments. Since Aedes genomes harbor nonretroviral Endogenous Viral Elements (nrEVEs) which confers tolerance to cognate viral infections in ovaries, we also tested whether nrEVEs are formed after CHIKV infection. We show that while small interfering (si)RNAs are evenly distributed along the full viral genome, PIWI-interacting (pi)RNAs mostly arise from a ~1000 bp window, from which a unique vDNA fragment is identified. CHIKV infection does not result in the formation of new nrEVEs, but piRNAs derived from existing nrEVEs correlate with differential expression of an endogenous transcript. These results demonstrate that all three RNAi pathways contribute to the homeostasis during the late stage of CHIKV infection, but in different ways, ranging from directly targeting the viral sequence to regulating the expression of mosquito transcripts and expand the role of nrEVEs beyond immunity against cognate viruses.